STUDY OF LEGAL PHENOMENCES IN SOCIETY FROM THE PERSPECTIVE OF LEGAL RELATIONS AND POWERS - Mulkan, Hasanal (Nurani, 2021)
The type of research used is normative research, legal research which is carried out by examining library materials that use the object of writing studies such as existing libraries, books, magazines, and regulations that have a correlation in problem discussion, so this writing is also writing library (library research).Various legal facts show the existence of power possessed by the state which does not aim to provide justice for society, whereas as it is known that the state is given power by the society on the basis of an agreement (social contract) in order to provide legal protection in the form of justice, one of them is reflected in the case of farmer mistreatment in Mesuji, Lampung due to seizure of land. Because the society feels that they do not get maximum justice as the goal of law in legal philosophy, so then the society can reclaim the power they have given to the authority. As for the basis used by the community in reclaiming the power they have given to the authority, because in the concept of “pactum subjectionis”, society has formed an agreement as to who deserves to hold power. After the agreement is made, the powers given to the state are legitimated by using social facts and laws.